2008
DOI: 10.1007/s10803-007-0527-5
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Screen Media for Persons with Autism Spectrum Disorders: Results of a Survey

Abstract: Social and anecdotal reports suggest a predilection for visual media among individuals on the autism spectrum, yet no formal investigation has explored the extent of that use. Using a distributed questionnaire design, parents and caregivers report on time allotted toward media, including observable behaviors and communicative responses. More time was spent engaged with electronic screen media (ESM) than any other leisure activity. Television and movie viewing was more popular than computer usage. Across media … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
119
1
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 217 publications
(126 citation statements)
references
References 14 publications
2
119
1
1
Order By: Relevance
“…Many parents report their children's fascination with and propensity for learning from visually based media such as computers (Nally et al 2000). In addition, researchers have identified that individuals with ASD not only demonstrate significant skill acquisition when taught via computers, but also have a preference for instruction delivered through such devices (e.g., Bernard-Opitz et al 2001;Moore et al 2000;Shane and Albert 2008). Given such preferences, the use of computer-assisted interventions (CAI) emerges as an ideal method for teaching students with ASD for several reasons.…”
mentioning
confidence: 99%
“…Many parents report their children's fascination with and propensity for learning from visually based media such as computers (Nally et al 2000). In addition, researchers have identified that individuals with ASD not only demonstrate significant skill acquisition when taught via computers, but also have a preference for instruction delivered through such devices (e.g., Bernard-Opitz et al 2001;Moore et al 2000;Shane and Albert 2008). Given such preferences, the use of computer-assisted interventions (CAI) emerges as an ideal method for teaching students with ASD for several reasons.…”
mentioning
confidence: 99%
“…In their tests the participants including those with Autistic disorder are tested on their communication, interaction and navigation abilities. Shane and Albert [27] supports the idea that the use of visual media based computer technology for those with Autism (ASD) would be beneficial due to their strong visual processing skills and predilection towards such media. Other research [28] is based on a multimedia computer game called emotional trainer which is used to teach those with Autistic Spectrum Disorders (ASD) to recognise and predict human emotional responses.…”
Section: The Use Of Computer Games For Cognitive Learningmentioning
confidence: 93%
“…First of all, game play makes therapy more exciting (Winkels et al 2012), which can be regarded as an efficient method (Shane & Albert 2008). Every child loves to play games.…”
Section: New Technologies On Rehabilitationmentioning
confidence: 99%